Verschiedene Bedeutungstypen bei den Entlehnungen aus dem Englischen im Dänischen - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2007)
The following article aims at presenting the changes in the scope of meaning of English loan-words in the Danish language. The ranges of meanings of loan-words tend to diverge from those of the original words: they can either be narrower or broader. Besides, there are instances of the so-called 'false friends', where the meanings are totally different. The article is meant to exemplify the phenomena rather than exhaust the inventory of loan-words.